Global portfolio network and currency risk premia - Jantke de Boer (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
The position of countries in a network of external portfolio investments provides a novel macroeconomic characteristic to explain violations of uncovered interest rate parity. I derive a network centrality measure, where central countries are highly integrated with key suppliers of tradeable financial assets. Currency risk premia decrease as network centrality increases. Asset pricing tests confirm that the centrality risk factor is priced in the cross-section. Further, negative global shocks appreciate central countries' currencies and depreciate peripheral ones. In a consumption-based capital asset pricing model, central countries experience lower consumption growth in high marginal utility states, leading to currency appreciation.
Keywords: F31; E43; E44; G12; G15; 330; Exchange rates; currency risk premia; external portfolios; financial network; asset pricing